Curving effects of concave dodecahedral nanocarbons enable enhanced Li-ion storage. Issue 30 (18th July 2018) - Liu, Huan; Zhang, Yaru; Dong, Jinyang; Ye, Tao; Hao, Jianmin; Yang, Yijun; Jiang, Xiangfen; Kang, Xiaohong; Bando, Yoshio; Wang, Xi
Abstract : Concave dodecahedral nanocarbons with highly curving concave faces and protuberant vertexes exhibit high specific capacity and superior cycle stability. Abstract : Dodecahedral nanocarbons with highly curving concave faces are synthesized via a one-step direct pyrolysis strategy. When tested as anodes in lithium-ion batteries (LIBs), the concave dodecahedral carbons (CDCs) show much enhanced capacity (∼2 times) and improved rate capability (603 mA h g −1 at 2000 mA g −1 ), when compared with the perfect ones without curved planes (PDCs, 280 mA h g −1 ). The curving effects of CDCs on Li ion storage are further investigated by constructing a CDC particle-based nanobattery device in an in situ transmission electron microscope (TEM). During the lithiation process of CDCs, the spacing in the curved parts expands much more than the perfect ones (from 0.5 nm to 0.7 nm), providing increasing active sites for Li ion storage. And the stable solid electrolyte interphase (SEI) layer and structural integrity for CDCs are also visualized during the discharge process, in good agreement with their ultralong cycle life. This design concept, enhancing curved parts in the structures, provides guidance in the development of next-generation advanced electrode materials.